Teori Permintaan Dalam Pandangan Islam - Muhammad Farid (EKSYAR : Jurnal Ekonomi Syari'ah & Bisnis Islam, 2014)
In conventional economic theory, the demand is a number of items to be purchased or requested at a certain price level within a certain time. While understanding the deals are a number of items sold or offered at a price and time. The law of demand is the law that describes the negative relationship between the price level in the quantity demanded. If the price of the quantity demanded rises slightly and when the low price the quantity demanded increases.